MARKET RESEARCH OF YOUNG (NEW) FROZEN POTATO - Vlahović, Branislav; R. Milanović, Milan (Economics of Agriculture, 2007)
Young (new) frozen potato represents nutrition of high quality, which is very important for consumers, because it has, beside others, very valuable nutritive characteristics. Primary goal of this research is to analyze the possibility for introducing new product to the market. Because this is a completely new product, it is necessary to do a market research and to take in consideration basic elements significant for distribution of the product. Data gathering has been done by opinion poll on a simple random sample of 300 people on the territory of Novi Sad. Although this is a relatively small sample for more significant representatively, gained answers are still enough indicative and they are pointing to basic factors which should determine placement of young (new) frozen potato.